LIFELONG LEARNING AS A PILLAR OF ENTREPRENEURSHIP IN THE GREEK COUNTRYSIDE - Dimitrios Ierapetritis; Dimitrios Lagos (European Regional Science Association (ERSA), 2010)
The development of business and innovation potential in the countryside depends on the availability of sufficient structures providing knowledge and skills on new technologies, while the most effective training process for farmers is an education based on the principles of experiential learning and adult education. The aim of this article is, based on the results of a nation-wide research addressed to farmers, instructors and head trainers, to explore and submit specific proposals for the reinforcement of entrepreneurship in the Greek countryside. More specifically, the aims sought through the results of this research, which was conducted among five hundred and ninety (590) trainee farmers, three hundred and twenty (320) instructors and fifty-eight (58) head trainers, are to bring forward the main attributes of farmers who wish to engage in entrepreneurial activities of the secondary and tertiary sector, to explore the aspects of the educational and administrative resources in the Greek countryside, to reveal their educational needs for successful business ventures and finally to put forward specific proposals both for promoting farmers' education and for the support of farmers who wish to enter the business field.
Keywords: 330; Entrepreneurship; exploring educational needs; lifelong learning; Greek countryside